Epilepsy spectrum disorders: A concept in need of validation or refutation. Issue 5 (November 2015) - Boutros, Nash N.; Bowyer, Susan; Wang, John; Urfy, Mian Z.; Loeb, Jeffrey A.
Abstract: Episodic psychiatric symptoms are not uncommon and range from panic attacks to repeated violent acts. Some evidence has accumulated over the years that at least in a subset of patients exhibiting these symptoms there may be evidence for the presence of focal cortical/subcortical hyperexcitability. In these cases the condition could be conceptualized as an epilepsy spectrum disorder (ESD) with significant treatment implications. There is currently no clear demarcation of this category of symptoms, their prevalence, an understanding of how these symptoms occur, what is appropriate work up and possible treatments. In this article, we propose that milder degrees of increased neural excitability (i.e., a subthreshold excitation insufficient to cause seizures) may nonetheless be capable of causing observable phenotypic changes. The observable phenotypic changes depend on the degree of hyperexcitability and the location of the hyperexcitable neural tissue. The location of the abnormal neural tissue may dictate the initial manifestation of an attack resulting from activation of the hyperexcitable tissue, but the anatomical connectivity of the abnormal region will dictate the breadth of manifestations. We provide some evidence, derived mainly from either electroencephalography studies of these populations or clinical reports of response to anti-epilepsy treatment, for the assumption and propose methods to test the advanced hypothesis.